Anisotropic behavior of grain boundary diffusion in hot-deformed Nd-Fe-B magnet. (1st March 2017) - Zhang, Tieqiao; Chen, Fugang; Zheng, Yan; Wen, Hongyuan; Zhang, Lanting; Zhou, Ligang
Abstract: Grain boundary diffusion process using Nd70 Cu30 was applied to the c-plane and ab-plane of hot-deformed Nd-Fe-B magnet. The coercivity was increased from 1.38 T to 2.44 and 2.20 T for the ab-plane and c-plane diffused specimens, respectively. The corresponding diffusion depth characterized by Cu content in the magnet was about 4.5 and 2.3 mm for the two specimens. Hierarchical coupling between "river-like" Nd-rich phase on the powder flake surface in micron-scale with the diffusion channels at the grain boundaries and triple junctions of the matrix grains in nano-scale is the fundamental cause of the anisotropic grain boundary diffusion behavior. Graphical abstract: